2013
DOI: 10.1177/1753495x13488771
|View full text |Cite
|
Sign up to set email alerts
|

The use of thrombolytic therapy in pregnancy

Abstract: The relative hypercoagulable state of pregnancy leads to an increased risk of thrombotic complications, of which some may be life-threatening or medically devastating. In the non-pregnant patient, the current guidelines suggest thrombolysis as the primary treatment in acute ischemic stroke, myocardial infarction when percutaneous intervention is unavailable, certain cases of mechanical valve thrombosis, and pulmonary embolism with hemodynamic compromise or shock. Given that clinical trial data regarding thromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 74 publications
0
37
0
3
Order By: Relevance
“…If PE is within a month of the expected date of delivery then a retrievable IVC filter should be inserted. A recent review identified 189 pregnant patients receiving thrombolysis for venous thromboembolism (VTE); major bleeding occurred in 2.6% with no maternal mortality 83. The peri-partum period poses a challenge with greater risk of haemorrhage associated with thrombolysis.…”
Section: Clinical Dilemmasmentioning
confidence: 99%
“…If PE is within a month of the expected date of delivery then a retrievable IVC filter should be inserted. A recent review identified 189 pregnant patients receiving thrombolysis for venous thromboembolism (VTE); major bleeding occurred in 2.6% with no maternal mortality 83. The peri-partum period poses a challenge with greater risk of haemorrhage associated with thrombolysis.…”
Section: Clinical Dilemmasmentioning
confidence: 99%
“…Thus it is unlikely that any thrombolytics will reach the fetus directly because they are all larger than 1000 Da. However, agents with larger molecular weights could presumably be preferred because the risk of reaching the fetus would be lowest . No registry exists to monitor pregnancy outcomes in women exposed to thrombolytics.…”
Section: Thrombolytic Agentsmentioning
confidence: 99%
“…Streptokinase undergoes insignificant placental transfer . However, a disadvantage of this agent is that it must be administered over 24 hours . Streptokinase is also associated with antibody development due to its nonspecific plasminogen binding, provoking allergic reactions and hypotension .…”
Section: Thrombolytic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Son yayınlanan Avrupa PE kılavuzunda trombolitik kullanılacak gebelerde doku-plazminojen aktivatörü (tPA) önerilmekte-dir (48). Bu konuda yakın zamanda yapılan bir derlemede 189 gebe hastada VTE için kullanılan trombolitik ilaçların anne mortalitesi artırmadan, %2.6 oranın-da majör kanamaya yol açtığı belirtilmiştir (49). Fare ve tavşan çalışmalarında tPA teratojenik etkisi göste-rilmemiştir (50).…”
Section: Gebelerde Trombolitik Tedaviunclassified